Gene expression profiles in human HepG2 cells treated with extracts of the Tamarindus indica fruit pulp. - Razali, N.; Aziz, A.A.; Junit, S.M. (2010)
Tamarindus indicaL. (T. indica) or locally known as asam jawa belongs to the family of Leguminosae. The fruit pulp had been reported to have antioxidant activities and possess hypolipidaemic effects. In this study, we attempted to investigate the gene expression patterns in human hepatoma HepG2 cell line in response to treatment with low concentration of the fruit pulp extracts. Microarray analysis using Affymetrix Human Genome 1.0 S.T arrays was used in the study. Microarray data were validated using semi-quantitative RT-PCR and real-time RT-PCR. Amongst the significantly up-regulated genes were those that code for the metallothioneins (MT1M, MT1F, MT1X) and glutathione S-transferases (GSTA1, GSTA2, GST02) that are involved in stress response. APOA4, APOA5, ABCG5 and MTTP genes were also significantly regulated that could be linked to hypolipidaemic activities of the T. indica fruit pulp.